2002
DOI: 10.1042/bst030a010b
|View full text |Cite
|
Sign up to set email alerts
|

The acetyl-group deficit limits mitochondrial ATP production at the onset of exercise

Abstract: The 'Cell-cell Lactate Shuttle' hypothesis posited that together with blood glucose, glycogen reserves in diverse tissues are mobilized to provide lactate, a metabolic intermediate that is either used within cells of formation or transported to adjacent and anatomically distributed cells for utilization. Hence, lactate was conceived to be a quantitatively important oxidizable substrate and gluconeogenic recursor. First with rats and 14C-tracers, then with humans and P3C-tracers we showed rapid lactate turnover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Of these, significant research attention has been paid to the pyruvate dehydrogenase complex (PDC), which irreversibly commits acetyl groups to the tricarboxylic acid cycle for oxidation. It has been demonstrated that preexercise activation of the PDC with dichloroacetate (DCA) can reduce substrate-level phosphorylation (SLP) (i.e., PCr hydrolysis and anaerobic glycolysis) early in exercise, and this has led to suggestions that oxidative metabolism must be greater in this condition (20). However, although there is evidence for a speeding of PiO 2 kinetics with DCA in the frog single-fiber model (22), no studies to date have been able to discern any effect of (1,17,24,35,53).…”
Section: Key Research Questionsmentioning
confidence: 99%
“…Of these, significant research attention has been paid to the pyruvate dehydrogenase complex (PDC), which irreversibly commits acetyl groups to the tricarboxylic acid cycle for oxidation. It has been demonstrated that preexercise activation of the PDC with dichloroacetate (DCA) can reduce substrate-level phosphorylation (SLP) (i.e., PCr hydrolysis and anaerobic glycolysis) early in exercise, and this has led to suggestions that oxidative metabolism must be greater in this condition (20). However, although there is evidence for a speeding of PiO 2 kinetics with DCA in the frog single-fiber model (22), no studies to date have been able to discern any effect of (1,17,24,35,53).…”
Section: Key Research Questionsmentioning
confidence: 99%
“…Control of oxidative phosphorylation during moderate-intensity exercise has been linked in some way to the creatine kinase reaction {e.g., cytosolic free [ADP] (5), phosphorylation potential ([ATP]/[ADP][P i ]) (59), or Gibbs free energy of ATP hydrolysis (⌬G ATP ) (45)}, and this is supported by the tight coupling of PCr breakdown and the phase II kinetics of pulmonary O 2 uptake (V O 2 ), reflecting muscle O 2 consumption (44,49). However, other factors, including O 2 availability (56) and activation of enzymes [e.g., pyruvate dehydrogenase (PDH)] and provision of substrates (16), have been also implicated to control oxidative phosphorylation at the onset of exercise.…”
mentioning
confidence: 99%
“…J Physiol 577.3 mitochondrial pyruvate dehydrogenase complex (PDH; Howlett et al 1999;Greenhaff et al 2002;Rossiter et al 2003;Howlett & Hogan, 2003). PDH has been proposed as a possible site of metabolic inertia as it controls the entry of carbohydrate-derived substrate into the tricarboxylic acid (TCA) cycle, and thus the provision of reducing equivalents (in the form of NADH and FADH 2 ) to the electron transport chain.…”
mentioning
confidence: 99%